Partial Contraction Analysis of Coupled Fractional Order Systems - Ahmad Ruzitalab; Mohammad Hadi Farahi; Gholamhossien Erjaee (Journal of Applied Mathematics)
Contraction theory regards the convergence between two arbitrary system trajectories. In this article we have introduced partial contraction theory as an extension of contraction theory to analyze coupled identical fractional order systems. It can, also, be applied to study the synchronization phenomenon in networks of various structures and with arbitrary number of systems. We have used partial contraction theory to derive exact and global results on synchronization and antisynchronization of fractional order systems.